VD_FINDINFO HC / 2016 / 152 vom 8. Februar 2016 - VD Tribunal cantonal (2016)
SERVITUDE, DROIT DE PASSAGE, CONTRAT DE SERVITUDE, DROIT DE VOISINAGE | 691 CC, 730 CC, 737 CC, 742 CC, 108 LATC, 58 al. 1 CPC (CH)